Dampak Kerja Sama Tim dan Jejaring Profesional dalam Peningkatan MSDM dengan Kolaborasi Lintas Fungsi Sebagai Variabel Intervening pada Dukcapil Kota Sungai Penuh - Zaber, Alif Dzaki Kholillah; Veri, Jhon (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the impact of teamwork and professional networks on human resource development, with cross-functional collaboration as an intervening variable at the Civil Registration Office (Dukcapil) of Sungai Penuh City. This is a quantitative study. The sample in this study consists of 30 employees of the Dukcapil of Sungai Penuh City. This study uses data analysis with the Partial Least Square (PLS) approach. The data analysis technique uses the R-Square value. The research results indicate that there is a positive and significant influence of professional networks on cross-functional collaboration among employees at Dukcapil City of Sungai Penuh. There is a positive and significant influence of teamwork on HR development improvement among employees at Dukcapil City of Sungai Penuh. There is a positive and significant influence of professional networks on HR development improvement among employees at Dukcapil City of Sungai Penuh. There is a positive but not significant influence of cross-functional collaboration on HR development improvement among employees at Dukcapil City of Sungai Penuh. Cross-functional collaboration does not mediate the effect of teamwork on HR development improvement among employees at Dukcapil City of Sungai Penuh. Cross-functional collaboration does not mediate the effect of professional networks on HR development improvement among employees at Dukcapil City of Sungai Penuh.